2009
DOI: 10.4103/0019-5545.58291
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of sexual dysfunction involving risperidone, quetiapine, and olanzapine

Abstract: Background:With the advent of newer antipsychotic drugs, side effects such as sexual dysfunction have been a major contributor toward treatment compliance. There are only a few studies that have compared different atypical antipsychotic agents regarding sexual dysfunction. We have not come across any data in this area on Indian population.Aims:To determine and compare the frequency of sexual dysfunction associated with risperidone, olanzapine, and quetiapine, among patients with clinically stable schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 20 publications
(30 reference statements)
3
39
1
1
Order By: Relevance
“…Further, this study showed that serum clozapine levels above 750 ng/ml increased the risk of seizures (odds ratio 5.15; p = 0.03) (Rajkumar et al 2013). Studies have also shown that use of typical antipsychotics leads to higher rates of sexual dysfunction (Nagaraj et al 2004;Nebhinani et al 2012), and among the atypical antipsychotics, sexual desire is more frequently impaired in subjects on risperidone and erectile dysfunction is more prevalent in subjects on olanzapine (Nagaraj et al 2001).…”
mentioning
confidence: 68%
“…Further, this study showed that serum clozapine levels above 750 ng/ml increased the risk of seizures (odds ratio 5.15; p = 0.03) (Rajkumar et al 2013). Studies have also shown that use of typical antipsychotics leads to higher rates of sexual dysfunction (Nagaraj et al 2004;Nebhinani et al 2012), and among the atypical antipsychotics, sexual desire is more frequently impaired in subjects on risperidone and erectile dysfunction is more prevalent in subjects on olanzapine (Nagaraj et al 2001).…”
mentioning
confidence: 68%
“…Orgazm bozuklu¤u, risperidon ve ketiapin grubunda eflit (%32) ve olanzapin grubunda %27 ora-n›nda bulunmufltur. Tüm cinsel yan etkiler aç›s›ndan bak›ld›¤›nda ketiapin grubunda, di¤er gruplara göre daha az etkilenme olmufl, ancak gruplar aras›nda anlaml› bir farkl›l›k görülmemifltir (42).…”
Section: Antipsikotiklere Ba¤l› Geliflen Cinsel ‹Fllev Bozukluklar›unclassified
“…There are sufficient studies that have looked into sexual dysfunction due to typical antipsychotics, as well as studies that have compared typical and atypical antipsychotic agents; however, there are only a few studies that have compared different atypical antipsychotic agents for sexual dysfunction [11].…”
Section: Introductionmentioning
confidence: 99%